Prevalence of the Genes Associated with Biofilm and Toxins Synthesis amongst the Pseudomonas aeruginosa Clinical Strains - Tomasz Bogiel; Dagmara Depka; Mateusz Rzepka; Joanna Kwiecińska-Piróg; Eugenia Gospodarek-Komkowska (Antibiotics, 2021)
Pseudomonas aeruginosa is one of the most commonly isolated bacteria from clinical specimens, with an increasing isolation frequency in nosocomial outbreaks. The hypothesis tested was whether carbapenem-resistant P. aeruginosa strains display an altered carriage of the virulence factor genes, depending on the type of carbapenem resistance. The aim of the study was to investigate, by PCR, the frequency of 10 chosen virulence factors genes (phzM, phzS, exoT, exoY, exoU, toxA, exoS, algD, pilA and pilB) and the genotype distribution in 107 non-duplicated carbapenem-resistant P. aeruginosa isolates. P. aeruginosa genes involved in phenazine dyes and exoenzyme T synthesis were noted with the highest frequency (100%). Fimbriae-encoding genes were detected with the lowest incidence: 15.9% and 4.7% for pilin A and B, respectively. The differences observed between the exoS gene prevalence amongst the carbapenemase-positive and the carbapenemase-negative strains and the pilA gene prevalence amongst the strains of different origins were statistically significant. Virulence genes’ prevalence and the genotype distribution vary amongst P. aeruginosa strains resistant to carbapenems, especially in terms of their carbapenemase synthesis ability and the strain origin.